The Dolichopus latipennis species group (=Hygroceleuthus Loew) in the Palearctic Region (Diptera: Dolichopodidae) - Negrobov, Oleg P.; Grichanov, Igor Ya; Barkalov, Anatolii V. (Zootaxa, 2009)
The Dolichopus latipennis species group in the Palearctic Region is reviewed. It comprises twelve species including two new Siberian species: Dolichopus tumicosta sp. nov. and D. lantsovi sp. nov. A revised key to species is provided, as well as remarks on the geographical distribution of the group.